Are You Dreaming? A Phenomenological Study on Understanding Lucid Dreams as a Tool for Introspection - Kitson, Alexandra; Schiphorst, Thecla; Riecke, Bernhard E. (CogSci Conference at SFU, 2017)
Lucid dreaming can be used as a tool for introspection and, ultimately, increase mental well being. What these experiences of introspection are like for lucid dreamers might be key to determining specific design guidelines for the future creation of a technological tool used for helping people to examine their own thoughts and emotions. The purpose of this study is to describe lucid dreamers’ representations of their introspective experiences. Using Creswell’s phenomenological method guidelines and LaBerge’s lucid dreaming methodology, a purposive sample of three active and proficient lucid dreamers were interviewed. The interviews were transcribed and coded in NVivo. From 71 significant statements, four themes emerged: Senses, Objects in the Dream, Experiences, and Meta. This knowledge of what participants experienced in terms of the phenomenon and how the experience happened can help design a system that is grounded in genuine experience and help keep the human condition intact.
Keywords: Riecke; Riecke_2017; alex-kitson; bernhard-riecke; lucid-dreaming; poster; posterWithoutPaper; talkWithoutPaper; thecla-schiphorst